Metal Combination Ceramic Jewelery Design with Inspiration of West Java Flora and Fauna - Maevara Audrey Saraswati; Sulistyo Setiawan (Aliansi Desainer Produk Industri Indonesia (ADPII), 2021)
The fast and dynamic growth of jewelry design makes designers collaborate with the artisan to develop innovation and uniqueness of jewelry design as characteristics and industrial's strength. One of Indonesia's riches that can be relied upon to be an inspiration is the diversity of typical flora and fauna of the regions in the archipelago. From these efforts, the jewelry industry can compete in both domestic and international markets. Besides, ceramic materials have not been using by the jewelry industry also acts as a differentiator between one business and its competitors. The purpose of developing jewelry designs using ceramic and metal materials is to produce innovative ceramic mix material jewelry products as an alternative product in the jewelry industry. The design research method used was shape exploration with a visual semantic approach. The result of this research is ceramic jewelry product can be used by the industry as an opportunity to keep innovate along with the development of fashion industry. Keywords: development, jewelry design, ceramic, metal.